2006
DOI: 10.1038/sj.jhh.1002127
|View full text |Cite
|
Sign up to set email alerts
|

Reverse white-coat effect as an independent risk for left ventricular concentric hypertrophy in patients with treated essential hypertension

Abstract: Recent studies have shown that the converse phenomenon of white-coat hypertension called 'reverse white-coat hypertension' or 'masked hypertension' is associated with poor cardiovascular prognosis. We assessed the hypothesis that this phenomenon may specifically influence left ventricular (LV) structure in treated hypertensive patients. A total of 272 outpatients (mean age, 65 years) with chronically treated essential hypertension and without remarkable white-coat effect were enrolled. Patients were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Two studies suggested that ME is an independent risk factor for target organ damage in treated hypertensive patients [2,3]. Tomiyama et al [2] showed that systolic ME is an independent risk factor for left ventricular concentric hypertrophy exclusively in treated hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies suggested that ME is an independent risk factor for target organ damage in treated hypertensive patients [2,3]. Tomiyama et al [2] showed that systolic ME is an independent risk factor for left ventricular concentric hypertrophy exclusively in treated hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Echocardiographic parameters were measured by the consensus of two experienced investigators who were blinded to the clinical data of the subjects. Measurements, such as interventricular septal thickness (IVSTd), posterior wall thickness (PWTd), LV diameter at end-diastole (LVDd) and LV diameter at end-systole (LVDs).…”
Section: Echocardiographic Measurementmentioning
confidence: 99%
“…8 Skorašnje studije su pokazale da je reverzna HBM važan prediktor u razvoju hipertro je leve komore. 9 Bolesnici sa drugim stadijumom arterijske hipertenzije imaju značajno češću pojavu cerebrovaskualrnih dogadjaja nego osobe sa nižim krvnim pritiskom a veruje se da bi osnov naglog poremećaja cerebralne cirkulacije mogao biti posledica dejstva pulsnog talasa, koji se prenosi duž aterijskih krvnih sudova. 10 Postoji saglasje da HBM ne treba lečiti medikamentima, bar u početnoj fazi.…”
Section: Strana / Page 33unclassified